ChemInform Abstract: Synthesis of Tetrasubstituted Pyrroles from Homopropargylic Amines via a Sonogashira Coupling/Intramolecular Hydroamination/Oxidation Sequence. Issue 6 (21st January 2016) - Wang, Chan; Huang, Kaimeng; Wang, Junying; Wang, Hongkai; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: 26 examples